Fürdőélet és közönség a tizenkilencedik századi Balatonfüreden - Katalin Vilma Kéri (Symbolon, 2021)
Bathing Life and Audience in the Nineteenth Century Balatonfüred Bath culture is one of humanity's oldest civilizational phenomena and – due to its historical, religious and geographical diversity – bears the characteristics of a particular age and society. In the nineteenth century, bathing was not only a way of cleansing, but also a way of life, where the preservation of health and healing were linked to the new concept of leisure time, including the arts. Through the history of theatre in Balatonfüred my research examines the composition of the spa from 1702 until the mid-nineteenth century. Balatonfüred played a regional role during the reform era. The essay analyses the spa visitors and audience’s impact on the life and theatre of Balatonfüred, covering the presence of the cultural and political elite of the nineteenth century, placing Balatonfüred on the palette of European bathing and theatrical culture.